2007
DOI: 10.1152/ajpcell.00064.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interactions of N1303K-CFTR and ENaC in Xenopus oocytes: evidence that chloride transport is not necessary for inhibition of ENaC

Abstract: Regulatory interactions of the cystic fibrosis transmembrane conductance regulator (CFTR) and the epithelial Na+ channel (ENaC) are readily apparent in Xenopus oocytes. However, the mechanism underlying these interactions remains controversial. CFTR's first nucleotide binding fold (NBD-1) may be important in these interactions, as dysfunctional CFTRs containing mutations within NBD-1, such as ΔF508 and G551D, lack such functional interactions with murine ENaC (mENaC). We hypothesized that a dysfunctional CFTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Furthermore, isolation of type II pneumocytes from TREK-1 deficient mice will allow us in future experiments to determine whether alterations in epithelial cell activation are contributing to the increased sensitivity to HO in these mice. Another important point to address in future studies is whether the effects of TREK-1 deficiency are related to alterations in cellular K + handling, or whether TREK-1 can exert functions that are unrelated to its role as a K + channel as for example described for CFTR[38, 39]. In a recently published study[40] we showed that TREK-1 regulates the mechanobiological properties of AECs by altering F-actin metabolism and overall cellular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, isolation of type II pneumocytes from TREK-1 deficient mice will allow us in future experiments to determine whether alterations in epithelial cell activation are contributing to the increased sensitivity to HO in these mice. Another important point to address in future studies is whether the effects of TREK-1 deficiency are related to alterations in cellular K + handling, or whether TREK-1 can exert functions that are unrelated to its role as a K + channel as for example described for CFTR[38, 39]. In a recently published study[40] we showed that TREK-1 regulates the mechanobiological properties of AECs by altering F-actin metabolism and overall cellular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ENaC by intracellular Cl − has also been proposed as an indirect mechanism for the regulation of ENaC by CFTR (Konig et al 2001; Bachhuber et al 2005). While this cannot be excluded as a physiological mechanism to regulate ENaC, CFTR mutants that can still conduct Cl − , such as N1303K, also fail to inhibit ENaC (Suaud et al 2007), suggesting that the exact mechanism whereby CFTR regulates ENaC remains unknown.…”
Section: Cftr–enac Interactions and Na+ Hyperabsorptionmentioning
confidence: 99%
“…Despite a precedence for this type of regulation of ENaC in mouse salivary duct epithelia [32], this hypothesis remains to be tested in the airways, and other investigators using Xenopus oocytes have reported that ENaC is still regulated appropriately following co-injection of αβγENaC and a non-Cl-conducting CFTR mutant [139]. The interaction between these two ion channels may be variable, and in the sweat glands, where Cl − absorption rather than Cl − secretion occurs under basal conditions, ENaC is activated in parallel with CFTR rather than being inactivated [115].…”
Section: Regulation Of Enac By Intracellular 2nd Messengersmentioning
confidence: 99%